Acidic ionic liquids catalyzed depolymerization of lignin - Dhepe, Paresh Laxmikant; Kelkar, Ashutosh Anant; Matsagar, Babasaheb Mansub; Singh, Sandip Kumar (WO2014181360 A1, 2014)
The present invention discloses a process for depolymerization of lignin to yield substituted phenolic monomers using Brönsted ionic liquid as catalyst under mild reaction conditions to obtain an overall yield of monomers up to 97%.